High concentration of blood cobalt is associated with the impairment of blood-brain barrier permeability. (June 2021) - Li, Zhigang; Wang, Ziye; Xue, Kaibing; Wang, Zhanshan; Guo, Chen; Qian, Yan; Li, Xiaoqian; Wei, Yongjie
Abstract: Excess heavy metals can lead to many kinds of adverse effects in human. The present study is designed to investigate whether the internal excess burden of heavy metals relate to the disturbance of the Blood-brain-barrier (BBB) and oxidative stress (OS) in subjects, and identify specific metallic constituents responsible for the disturbance. We collected the blood from recruited 122 subjects for our comparison study, 69 were living at an area near e-waste dismantling factories (exposed group), who have higher levels of heavy metals in the body; and others were in a chosen reference area (reference group), who were the general residents in city, in December 2017 in Taizhou, Zhejiang province. The analyses showed that the concentrations of altogether 4 metals, including nickel (Ni), cobalt (Co), mercury (Hg) and stannum (Sn), and the triggers of BBB disruption (Apolipoprotein E4 and matrix-metalloproteinase-9), indicators of BBB (Myelin basic protein, serotonin and dopamine) and biomarkers of OS (Malondialdehyde and 8-isoprostane) were statistically significant higher in exposed group than in reference group. Moreover, they are also significantly positively correlated with each other. Among all the metals, both Pearson correlation and multiple linear regression showed Co was positive correlated with almost all biomarkers. Considering the explicit correlation between Co and BBB permeability, we speculated that high burden of Co in blood may have a connection with neurodegenerative diseases, which propose a requirement for constructing the environmental criteria for Co and might provide a potential new hint for the intervention of dementia. Graphical abstract: Image 1 Highlights: E-waste exposed elevated the level of Ni, Co, Hg and Sn in blood. E-waste exposed elevated the level of indicators of blood-brain-barrier (BBB) in blood. E-waste exposed elevated the level of biomarkers of oxidative stress (OS) in blood. Blood Co correlated with the indicators of BBB and biomarkers of OS.